Analysis of the Content of the Da'wah Message in The Lyrics of "No Burden Without Shoulders" by Edcoustic - Roni Rodiana; Muhamad Nursubanudin Alwi; Ario Ainal Yakin (Zona Education Indonesia, 2023)
Basically, in order for the message of da'wah to be conveyed easily in society, a da'i must be able to adjust what is the habit of the community in behavior, culture and others. In short, what has always been their habit, that's where a preacher can make it a means of da'wah. In this study, the method is very important for a study to get the desired data more accurately. In this study, the author uses qualitative research methods, namely research that does not carry out calculations, where the data is not in the form of numbers but words that are described. The song studied is the lyrics of a song entitled "No Burden Without Shoulders", this song is contained in the nasyid group EdCoustic, the meaning to be conveyed is the meaning of the message of da'wah about narrowness of heart and spaciousness of heart. The phrase spaciousness of the heart is very often heard by everyone, but not everyone tries to ask for his heart to be given spaciousness and not everyone stops trying to have his chest expanded. The author analyzes the lyrics of Nasyid Tak Ada Burden Tanpa Pundak in formulating the message of da'wah is very easy and effective